2016
DOI: 10.1038/hortres.2015.67
|View full text |Cite
|
Sign up to set email alerts
|

Sugars in peach fruit: a breeding perspective

Abstract: The last decade has been characterized by a decrease in peach (Prunus persica) fruit consumption in many countries, foremost due to unsatisfactory quality. The sugar content is one of the most important quality traits perceived by consumers, and the development of novel peach cultivars with sugar-enhanced content is a primary objective of breeding programs to revert the market inertia. Nevertheless, the progress reachable through classical phenotypic selection is limited by the narrow genetic bases of peach br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
136
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 154 publications
16
136
0
3
Order By: Relevance
“…This result agreed with the previous finding that both fructose and sorbitol contents are less influenced by the prevailing environmental conditions over the growing season than other sugars (Cantin et al ., ). This association signal for sorbitol was close to an important QTL previously reported for the control of fructose, glucose and sorbitol contents, the total sugar content and the SSC (Abbott et al ., ; Cirilli et al ., ; Salazar et al ., ). Our results indicated that the control of complex domestication traits in peach may have resulted from a combination of minor effect QTLs that are unstable across years, as reported for perennial fruit crops in general by Miller and Gross ().…”
Section: Discussionmentioning
confidence: 98%
“…This result agreed with the previous finding that both fructose and sorbitol contents are less influenced by the prevailing environmental conditions over the growing season than other sugars (Cantin et al ., ). This association signal for sorbitol was close to an important QTL previously reported for the control of fructose, glucose and sorbitol contents, the total sugar content and the SSC (Abbott et al ., ; Cirilli et al ., ; Salazar et al ., ). Our results indicated that the control of complex domestication traits in peach may have resulted from a combination of minor effect QTLs that are unstable across years, as reported for perennial fruit crops in general by Miller and Gross ().…”
Section: Discussionmentioning
confidence: 98%
“…The traits used in this study are largely polygenic (FW: [45] SC: [46]) and thus well suited for GBLUP and similar approaches (like SNP/RR-BLUP e.g. [47]), which build on the hypothesis of many small additive allele contributions to the phenotype (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Sweetness perception of fruits depends on the balance between sugars and acids (Cirilli et al, 2016;Farneti et al, 2017). For the sugar content, measured as the soluble solids content, two significant SNPs occurred at genes encoding proteins with a role in the ubiquitin-mediated protein degradation pathway.…”
Section: Biological Insights Into the Genetic Basis Of Fruit-relatedmentioning
confidence: 99%